Synthesis and Spectral Studies of Co(II),Ni(II),Zn(II) and Cd(II) Complexes with Ligand 2-[4- Carboxy methyl phenyl azo] -4,5-diphenyl imidazole (4CMeI) (Baghdad Science Journal, 2013)
A new chelate complexes of Co(II),Ni(II),Zn(II) and Cd(II) were prepared by reacting these ions with the ligand 2-[4- Carboxy methyl phenyl azo]-4,5-diphenyl imidazole (4CMeI) The preparation were conducted after fixing the optimum conditions such as (pH) and concentration .UV- visible spectra of these complex solutions were studied for a range of (pH) and concentration which obey lampert-Beers Law.The structures of complexes were deduced according to mole ratio method which were obtained from the spectroscopic studies of the complex solutions .The ratios of metal: ligand obtained were (1:2) for all complexes..(UV-Vis) absorption spectra and The infrared spectra of the chelating complexes were studied ,this may indicate that coordination between the metal ions and our ligand takes place.The conductivity measurements , elemental analysis ,the percentage of some metal ions and the measurements of magnetic susceptibility of the complexes were determined ,Depending on these results , in addition to, We may conclude that the ligand was bidentate Also the proposed geometrical structures of the complexes of Co(II), Ni(II), Zn(II) and Cd (II) ions are octahedral